Discriminatory attitudes against unvaccinated people during the pandemic - Bor, Alexander; Jørgensen, Frederik; Petersen, Michael Bang (Nature (London), 2023)
During the COVID-19 pandemic, sizeable groups of unvaccinated people persist even in countries with high vaccine access 1 . As a consequence, vaccination became a controversial subject of debate and even protest 2 . Here we assess whether people express discriminatory attitudes in the form of negative affectivity, stereotypes and exclusionary attitudes in family and political settings across groups defined by COVID-19 vaccination status. We quantify discriminatory attitudes between vaccinated and unvaccinated citizens in 21 countries, covering a diverse set of cultures across the world. Across three conjoined experimental studies ( n = 15,233), we demonstrate that vaccinated people express discriminatory attitudes towards unvaccinated individuals at a level as high as discriminatory attitudes that are commonly aimed at immigrant and minority populations 3 — 5 . By contrast, there is an absence of evidence that unvaccinated individuals display discriminatory attitudes towards vaccinated people, except for the presence of negative affectivity in Germany and the USA. We find evidence in support of discriminatory attitudes against unvaccinated individuals in all countries except for Hungary and Romania, and find that discriminatory attitudes are more strongly expressed in cultures with stronger cooperative norms. Previous research on the psychology of cooperation has shown that individuals react negatively against perceived ‘free-riders’ 6 , 7 , including in the domain of vaccinations 8 , 9 . Consistent with this, we find that contributors to the public good of epidemic control (that is, vaccinated individuals) react with discriminatory attitudes towards perceived free-riders (that is, unvaccinated individuals). National leaders and vaccinated members of the public appealed to moral obligations to increase COVID-19 vaccine uptake 10 , 11 , but our findings suggest that discriminatory attitudes—including support for the removal of fundamental rights—simultaneously emerged. Vaccinated people express discriminatory attitudes towards unvaccinated individuals across cultures.